Antiviral activity of dandelion aqueous extract against pseudorabies virus both in vitro and in vivo - Cai, Xiaojing; Shao, Yi; Wang, Zhiying; Xu, Yongkang; Ren, Zhiyuan; Fu, Lian; Zhu, Yan (Frontiers in Veterinary Science, 2023)
Pseudorabies virus (PRV) is one of the most significant pathogens of swine. In recent years, the continual emergence of novel PRV variants has caused substantial economic losses in the global pig industry. PRV can infect humans leading to symptoms of acute encephalitis with implications for public health. Thus, new measures are urgently needed to prevent PRV infection. This study evaluated the anti-PRV capability of dandelion aqueous extract (DAE) in vitro and in vivo. DAE was found to inhibit the multiplication of the PRV TJ strain in PK15 cells in a concentration-dependent manner, with a 50% inhibitory concentration (IC50) of 0.2559 mg/mL and a selectivity index (SI) of 14.3. DAE inhibited the adsorption and replication phases of the PRV life cycle in vitro, and the expression of IE180, EP0, UL29, UL44, and UL52 was inhibited in the presence of DAE. In vivo experiment results of mice show that a 0.5 g/kg dose of DAE injected intraperitoneally protected 28.6% of the mice from the lethal challenge; decreased the viral load in the liver, lung, brain, heart, and kidney of PRV-infected mice; and attenuated brain damage caused by PRV infection. Furthermore, DAE could also ameliorate viral infection through regulation of the levels of cytokines (IFN-γ, TNF-α, and IL-4) in PRV-infected mouse serum. These results demonstrated that DAE exhibited potent inhibitory capability against PRV infection in vitro and in vivo; DAE is therefore expected to be a candidate TCM herb for use against PRV infection.